The assessment of postural control and the influence of a secondary task in people with anterior cruciate ligament reconstructed knees using a Nintendo Wii Balance Board. Issue 14 (25th December 2012) - Howells, Brooke E; Clark, Ross A; Ardern, Clare L; Bryant, Adam L; Feller, Julian A; Whitehead, Timothy S; Webster, Kate E
Abstract : Background: Postural control impairments may persist following anterior cruciate ligament (ACL) reconstruction. The effect of a secondary task on postural control has, however, not been determined. The purpose of this case–control study was to compare postural control in patients following ACL reconstruction with healthy individuals with and without a secondary task. Participants: 45 patients (30 men and 15 women) participated at least 6 months following primary ACL reconstruction surgery. Participants were individually matched by age, gender and sports activity to healthy controls. Materials: Postural control was measured using a Nintendo Wii Balance Board and customised software during static single-leg stance and with the addition of a secondary task. The secondary task required participants to match the movement of an oscillating marker by adducting and abducting their arm. Main outcome measures: Centre of pressure (CoP) path length in both medial-lateral and anterior–posterior directions, and CoP total path length. Results: When compared with the control group, the anterior–posterior path length significantly increased in the ACL reconstruction patients' operated (12.3%, p=0.02) and non-operated limbs (12.8%, p=0.02) for the single-task condition, and the non-operated limb (11.5%, p=0.006) for the secondary task condition. The addition of a secondary task significantly increased CoP path lengths in all measures (p<0.001), although the magnitude of the increase was similar in both the ACL reconstruction and control groups. Discussion: ACL reconstruction patients showed a reduced ability in both limbs to control the movement of the body in the anterior–posterior direction. The secondary task affected postural control by comparable amounts in patients after ACL reconstruction and healthy controls. Devices for the objective measurement of postural control, such as the one used in this study, may help clinicians to more accurately identify patients with deficits who may benefit from targeted neuromuscular training programs.